Active Packaging Film of Starch and Chitosan Incorporated with Beetroot Extract for Improvement of Quality and Shelf Life of Chicken Patties - Yadav, Vishwa Jeet; Shukla, V. H.; Zende, R. J. (Journal of Meat Science, 2022)
The present work evaluated the effect of edible film of starch and chitosan  incorporated with beetroot extract on improving chicken patties’ quality  and shelf life. The chicken patties coated with an edible film of starch and  chitosan (T1) and chicken patties coated with an edible film of starch  and chitosan incorporated with beetroot extract (T2) were compared  with patties without any coating (control). The results revealed that T2 had significantly lower (P0.05) on the sensory characteristics of patties during storage. The  application of starch-chitosan edible film and beetroot extract extended  chicken patties’ shelf-life by 8 to 10 days.
Keywords: Active Packaging; Edible film; eet Root Extract; Natural Preservation